ANALYZING THE EFFECT OF PERCEIVED VALUE AND TRUST ON PURCHASE INTENTION (Case Study of Zalora) - Kawet, Octodavid; Pangemanan, Sifrid S.; Tumiwa, Johan (Universitas Sam Ratulangi, 2017)
Abstract: With advance progress of marketing, nowadays people don’t have to waste their time walking to the store to buy things. They only need to browse the internet and search for what they want and get it in no time. With this convenience in mind, the interest in online shopping is increasing. When customers intent to purchase product from the internet, they consider about perceived value and trust. The main objective of this study is to analyze the effect of perceived value and trust on purchase intention of Zalora. The data was collected from 100 respondents and multiple regression analysis was used to test the relationship among variables. Based on indicators explained in perceived value which are experimental value, functional value, market value and trust which are ability, benevolence, integrity they has a significant partial effect on purchase intention. The result can be maintain by giving the customer the best value and obtain their trust to sustain their purchase intention.Keywords: online shop, purchase intention, perceived value, trust